A Method for Quality Assessment of Image Resizing Algorithms - Asatryan, David; Kurkchiyan, Vardan; Bagramyan, Marine (Mathematical Problems of Computer Science, 2021)
In this paper, a novel technique for quality assessment of image resizing algorithms is proposed. The technique is based on consecutive application of a resizing algorithm with different resizing coefficients so that the size of the last image coincide with the size of the original image. The Mean square deviation between the last and the original image characterizes the quality of applied resizing algorithm, which can be called the “backlash” of that algorithm. Numerical results of experiments are given to show the effectiveness of proposed technique.